Pooling the complex survey data across the 64 lower and middle-income countries: A study on antibiotic usage in under-five children - Md Fakrul Islam; Prosenjit Basak Arka; Mahfuzer Rohman; Md Sabbir Hossain; Md Rashed Babu; Hasin Anupama Azhari; Md Jamal Uddin (Heliyon)
Background: Antibiotic exposure for fever/cough has been rising alarmingly, especially among children under five in low- and middle-income countries (LMICs). This excessive use could result in higher healthcare costs, and antibiotic resistance is an alarming trend in developing countries. As a result, it's crucial to look at the variables that affect antibiotic exposure and highlight the subgroups among whom antibiotic abuse is the most prevalent. Methods: We used the most recent standard Demographic and Health Survey (DHS) data for 64 LMICs. Sample weights were employed in studies to ensure exact standard errors and estimate p-values. To analyze antibiotic exposures across countries, continents, economic levels, and the top and bottom ten countries with fever/cough, we conducted descriptive statistics. Additionally, we provided accompanying bar diagrams for each descriptive finding to enhance visual understanding. For geospatial analysis, we utilized ArcGIS, a powerful tool for mapping and spatial analysis. Findings: We used data from 141,018 children under five who were reported to have had fever/cough recently in 64 LMICs. Among them, 30.4 % were exposed to antibiotics for fever/cough. Congo (68.7 %), Egypt (65.5 %), and Tajikistan (61.8 %) had the highest prevalence of antibiotic consumption across LMICs. On the other hand, Cameroon (0.3 %), Armenia (4.0 %), and Mauritania (6.1 %) had the lowest. In the final binary logistic regression, mothers that had any formal education (Primary: OR = 1.28, 95 % CI:1.07–1.53, Secondary: OR = 1.38, 95 % CI:1.14–1.67, Higher Education: OR = 1.69, 95 % CI:1.23–2.33) were more likely to expose their children to antibiotics for fever/cough than illiterate ones. Additionally, children in richer households (Richer: OR = 1.38, 95 % CI:1.15–1.66, Richest: OR = 1.46, 95 % CI:1.19–1.80) were more likely to receive antibiotics than those in poorer households. Conclusions: Antibiotic exposure for fever/cough in children under five was relatively moderate across 64 LMICs. However, the rate was incredibly high in some LMICs and incredibly low in others. The researchers recommend that the countries with high and low percentages of antibiotic exposure investigate either any possibility of antibiotic abuse or proper healthcare service at the national level.